The treatment with an anti-glycosaminoglycan antibody reduces aortic oxidative stress in a rabbit model of atherosclerosis. (April 2013) - Delgado-Roche, L.; Acosta, E.; Soto, Y.; Hernández-Matos, Y.; Olivera, A.; Fernández-Sánchez, E.; Vázquez, A. M.
Abstract Retained low-density lipoproteins (LDL) by arterial glycosaminoglycans (GAG) are more susceptible to reactive oxygen species-mediated oxidation, contributing to oxidative stress and atherosclerosis. Recently, we reported the properties of the chimeric mouse/human monoclonal antibody chP3R99-LALA to bind sulfated GAG, to inhibit LDL-chondroitin sulfate binding, and to avoid LDL oxidation in vitro. Here, we hypothesized that chP3R99-LALA treatment might reduce aortic oxidative stress in a therapeutic setting. Redox biomarkers and serum lipids were determined by spectrophotometric methods. Subcutaneous administration of five doses (100 μg) of chP3R99-LALA, after Lipofundin administration (2 mL/kg/day, i.v.) during 8 days, reduced atherosclerotic lesion development, which was not associated with a serum lipid modulation. In contrast, the treatment with chP3R99-LALA reduced (p < 0.05) malondialdehyde and protein oxidation, induced a restoration of reduced glutathione level, of the superoxide dismutase and catalase activities and of endothelial nitric oxide level. Thus, the antiatherogenic effect of chP3R99-LALA treatment seems to be associated with a reduction of aortic oxidative stress. These results contribute in understanding the molecular mechanisms associated with chP3R99-LALA atheroprotection and support the use of anti-GAG antibody-based immunotherapy as a potential tool to treat the atherosclerosis.